Extension of the use of cellulose nanowhiskers in composite materials - Hossain, Kazi Md Zakir (2014)
This thesis explores the use of cotton derived cellulose nanowhiskers (CNWs) in composite materials in the form of nanocomposite films, surface modified polymer fibres and also in self-reinforced (SR) composites.